Los nuevos precarios, ¿mujeres u hombres? Tendencias en el mercado de trabajo urbano en Panamá, 1982-1999 - Castillo-Fernández, Dídimo (Papeles de Población, 2021)
The emergent economic globalization processes have induced, at least, two trends in environment of labor markets: firstly, one given by the increase in women economic participation, and therefore, the feminization of salaried labor: and the other by the expansion in the ways of hirig and usage of labor force. The study presents a detailed survey on both trends in the region from a gender approach. I assume that there is an increase in precarization of labor which is diferential from men to woman. There is a revision on urban occupation structure in Panama based on the information obtained from a households survey, and the patterns in precarization for total occupied population is analyzed, as well as for sex structure, considering some basic indicators. Finally, a precarization index using multivariate technique of principal component is estimated.